2019
DOI: 10.1029/2019jd031503
|View full text |Cite
|
Sign up to set email alerts
|

A Damping Effect of the Maritime Continent for the Madden‐Julian Oscillation

Abstract: The damping effect of the Maritime Continent (MC) on propagation of the Madden‐Julian Oscillation (MJO) has been widely recognized; however, its underlying physics remains largely elusive. Capitalizing on the latest high‐resolution reanalysis data (ERA‐5) from the ECMWF, analyses in this study suggest that the interruption of lower‐tropospheric moistening over the MC land during MJO eastward propagation is mainly due to a drying effect induced by zonal advection of the low‐level winter mean moisture by MJO win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 90 publications
(143 reference statements)
1
18
0
Order By: Relevance
“…While this study highlights the role of the basic state moisture in the simulation of the MJO, our understanding of the processes that control the mean state moisture around the MC is still limited. Jiang et al (2019) suggested that the MC diurnal cycle and topography play an important role on the formation of the mean state moisture around the MC. The improvement in the mean state moisture around MC in CMIP6 models is possibly due to the increased horizontal resolution, thus a better representation of MC island effects.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…While this study highlights the role of the basic state moisture in the simulation of the MJO, our understanding of the processes that control the mean state moisture around the MC is still limited. Jiang et al (2019) suggested that the MC diurnal cycle and topography play an important role on the formation of the mean state moisture around the MC. The improvement in the mean state moisture around MC in CMIP6 models is possibly due to the increased horizontal resolution, thus a better representation of MC island effects.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Also, in the model experiments with disabled diurnal cycles or modified MC topography, the simulated changes to MJO propagation behavior are due to not only the diurnal cycle and MC topography but also associated changes in the large‐scale mean state. For example, as previously discussed, the strong topographically phase‐locked mean moisture pattern over the MC, which strongly interrupts MJO moist preconditioning over the eastern part of the MC mountains, is largely defined by the diurnal cycle (Jiang et al, 2019). If the diurnal cycle is disabled in a model, the regional mean moisture gradient will be significantly weakened, which favors a smooth eastward MJO propagation over the MC (Hagos et al, 2016; Oh et al, 2013).…”
Section: Recent Progress In Understanding Modeling and Predicting Tmentioning
confidence: 96%
“…Hung & Sui, 2018; Jiang et al, 2019). Strongly shaped by the local diurnal cycle, the low‐level winter mean moisture pattern over the MC is characterized by moisture maxima over local mountain peaks (Jiang et al, 2019). Given this mean moisture distribution, the moisture advection by anomalous easterly MJO winds corresponding to the active MJO convection over the eastern Indian Ocean will lead to a drying (moistening) effect to the east (west) of the mountain peaks, which disrupts the organization of large‐scale MJO convection over the MC area.…”
Section: Recent Progress In Understanding Modeling and Predicting Tmentioning
confidence: 99%
See 1 more Smart Citation
“…They further suggested that ENSO influences the transient dry precursors by modifying the background moisture. Using ERA5 reanalysis, Jiang et al (2019) showed that MC topography interrupts the moistening that supports eastward propagation of the MJO by modifying the seasonal mean zonal distribution of moisture and the associated advection moistening. In another recent study, Hagos et al (2019) estimated the moisture flux convergence directly from precipitation and showed the slow eastward migration of zonal moisture flux convergence between the Asian and Australian monsoon convergence centers from summer to winter.…”
Section: Introductionmentioning
confidence: 99%